Analysis of Quality Control in Black Tea Drying Process with Six Sigma Methods: Case Study in PTPN XII (Persero) Wonosari, Lawang - Januar, M.; Astuti, Retno; Ikasari, Dhita Morita (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Drying process was one of the CCP (Critical Control Point) in black tea manufacturing process.The purpose of this study were determining the sigma value of drying process on black tea manufacture determining the factors causing the process deviations and providing recommendation of priority improvement to reduce defects in the drying process in PT. Perkebunan Nusantara XII (Persero) Wonosari, Lawang. Measurements were performed by using the method of six sigma (define, measure and analyze) and FMEA (Failure Modes and Effects Analysis). The research result showed that the six sigma level in short-term process capability was 2.28 and the six sigma level in long term process capability was 2.41. Thesesigma value levelwere considered to be good for the company in Indonesia, because these value were over of 2 sigma which was standard sigma value in Indonesia. Factors causing deviations of drying process are methods, machine and the environment.The priority for improvement was carried out on failure modes with the biggest RPN value which was 252. This priority was on machine maintenance which was poor, such as a rare checking machine.Keywords: Quality Control, Drying Process, Six Sigma